Russian-Ukrainian Conflict: International Humanitarian Law and Civilian Settlements - Gunawan, Yordan; Gultom, Qinnara Zegia; Amarulia, Shafirah; Arumbinang, Mohammad Hazyar (Susbtantive Justice International Journal of Law, 2023)
The research analyzes the views of the International Humanitarian Law (IHL) and UN Charter violations in the case of the invasion of civilian settlements in the Russia-Ukraine conflict for justice. The conflict, which took place on February 24, 2022, has raised serious concerns about violations of the UN Charter and IHL and the protection of civilians. This research collected data and information from various primary and secondary sources, including reports of international organizations, legal documents, and journal analysis. A qualitative approach was used to analyze the impact of the invasion of civilian settlements on IHL in the case of the Russia and Ukraine case. The results show that the view of IHL in the context of the invasion of civilian settlements in the Russia-Ukraine case has caused great harm to civilians, ranging from damage to homes, infrastructure, and public facilities, including casualties. It also appears that Russia has ignored the guiding principles of the UN Charter. To overcome this problem, several steps can be taken. First, there is a need to increase understanding and awareness of IHL among all parties involved in the conflict. Second, increase efforts to maintain brotherhood between nations. Third, working together to assist in humanitarian terms in the event of armed conflict, famine, and starvation. The resulting policy implications and recommendations can be used as a guide for policymakers and practitioners to improve the humanitarian protection of civilians in the future.